SPECIFIC CHARACTERISTICS OF TOUR OPERATOR ACTIVITY MANAGEMENT - Mamadaliev Toxirjon ugli, Ulugbek (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The distinctive features of tour operator management include several important strategic, operational and customer-oriented services. This will further develop the field of activity of tour operators in the industry, moving between technology and innovation and consumer preferences. In this article, we will look at the specifics of tour operator management, strategic positioning, organizational needs, and key aspects of customer engagement within the tour operator business.